Three dimensional liquid and vapour distribution in the wick of capillary evaporators. (April 2015) - Mottet, L.; Coquard, T.; Prat, M.
Abstract: Heat and mass transfer with liquid–vapour phase change in a representative unit cell of a capillary evaporator is studied using a mixed pore network model. The model combines the computation of temperature and pressure fields in vapour and liquid pores according to mean field approaches with pore scale invasion rules depending on the capillary pressure thresholds associated with each local constriction between two pores. The metallic body through which heat is transferred to the porous wick is also taken into account in the simulations. After comparisons with a visualisation experiment, numerical simulations performed in three dimensional pore networks lead to the identification of three main regimes depending on the applied heat load. Compared with previous works using the so-called vapour pocket assumption, the 3D simulations reveal a regime where the phase distribution within the wick is fundamentally different. This regime is characterised by the coexistence of both the liquid and vapour phases underneath the casing within the wick. This regime is shown to correspond to the best evaporator performance.